Pengaruh Return on Aset dan Ukuran Perusahaan Terhadap Tax Avoidance - Hadi Sutomo (LPMP Imperium, 2022)
This study aims to determine the return on assets and company size that affect tax avoidance. Secondary data was collected from companies listed in the chemical industry sub-sector listed on the Indonesia Stock Exchange for 2014 – 2017. Sampling in this study was a purposive sampling method, and the criteria were: (1) Manufacturing companies in the primary and chemical industries listed on the IDX for the period 2014-2017; (2) The data belonging to the company must be complete and based on the variables studied. The data needed in this study was obtained through the 2014-2017 Indonesian Capital Market Directory (ICMD). This study uses multiple linear regression analysis: to test the partial, it requires t statistical testing and simultaneous testing using the ANOVA statistical test, and before carrying out this test, the classical assumption test is first. The results of the study show that if Return on Assets affects Tax Avoidance, then the size of the company without affecting the value of the company